Experimental and Numerical Studies on Vibration Modes and Transcranial Attenuation Characteristics in Unilateral Bone Conduction Hearing. (1st June 2020) - Li, Jia; Ren, Liujie; Wu, Tongge; Yin, Dongming; Dai, Peidong; Chen, Lifen; Zhang, Tianyu
Abstract : Bone conduction (BC) hearing devices have been used to improve hearing in patients with unilateral conductive hearing loss; however, the clinical results of improvement in the sound localization ability are still controversial. Transcranial transmission in BC may be an important factor affecting sound localization abilities. Transcranial or interaural attenuation, derived from energy attenuation during the BC process, is determined by the different transfer functions of multiple pathways and affected by the whole-head vibration modes. The purpose of this study is to analyze the frequency dependence of BC vibration modes of the whole head, the contribution of middle and inner ear pathways to BC hearing, and the relationship between transcranial attenuation results by dynamics measurement and hearing thresholds. Experimental studies of vibration modes and transcranial attenuation characteristics in BC are performed using scanning laser Doppler vibrometry (LDV) measurements on human cadaver heads. Differences in vibration modes between the excitation and contralateral sides are observed. Additionally, a multiscale human whole-head FE model, including the skull, bony outer ear, ossicular chains, and bony inner ear structures, is proposed to study the mechanism of BC in the human hearing system. After verifying the rationality of the FE model using mechanical impedance and frequency response data, the transcranial attenuation on the temporal bone surfaces and the middle ear structure is calculated in the FE model. Moreover, the vibration characteristics of bilateral ossicular chains and the cochlear bony wall are observed in the whole-head FM model to study their contributions to BC hearing. By analyzing the experimental and numerical results of the vibration modes and the frequency response of the whole head incorporating the ossicular chain and cochlear bony wall, the intrinsic relationship between the results of transcranial attenuation by 1D LDV, 3D LDV, and hearing threshold measurements is further investigated.